Early school leaving. RESL project. RONI and its adatation to Barcelona context - Mercè Berengueras Pont; Xavier Chavarria Navarro; Jordi Serarols (ADIDE Federación, 2014)
The Inspectorate of Barcelona coordinates a project that FEAEC (European Forum of Educational Administrators of Catalonia) and six secondary schools are involved: Ernest Lluch, Miquel Tarradell, and La Guineueta (public schools) and Joan Pelegri, Proa, and Virolai (private schools founded by the state). This is a "Comenius Regio" Regional Development Programme 2013-2015 between Sheffield and Barcelona with reference to the theme: "Reducing Early School Leaving" (RESL). The Council of Europe establish Early School Leaving as "the percentage of young people between 18 and 24 years, at most, have passed the compulsory secondary education and not in education nor training continue". In our country, we are concerned about students who complete lower secondary education, although we cannot forget that the objectives of the Spanish and European political system success lie in universal upper secondary they can graduate. One of the products developed in the project has been the adaptation of RONI (an individual indicator of risk of dropouts) and its experimental application.